The Role of Anti-Corruption Agencies in the Investigation and Prosecution of Procurement Related Corruption Cases - Annika Engelbert (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2014)
In most developing countries, anti-corruption agencies were established in compliance with international treaties to prevent and combat corruption through law enforcement. Yet conviction rates in corruption have remained very low, undermining the deterrent effect arising from a high risk of detection. Whereas previous research has focused on identifying external success factors for anti-corruption agencies, this paper argues that effective collaboration mechanisms between these agencies, monitoring bodies in corruption-prone sectors such as public procurement, and public prosecution are crucial for curbing corruption. By means of a comparative case study of Tanzania and Uganda, it shall be explored whether a more streamlined or dispersed collaboration approach is more promising in a highly corrupt setting. Besides national laws, the analysis is based on findings from expert interviews and on reports by procurement authorities and the media.
Keywords: 330; Corruption; Anti-corruption agencies; Tanzania; Uganda; Anti-Korruption; Öffentlicher Auftrag; Tansania; Uganda